2022
DOI: 10.3390/fishes7050234
|View full text |Cite
|
Sign up to set email alerts
|

Statolith Microstructure Estimates of the Age, Growth, and Population Structure of Purpleback Flying Squid (Sthenoteuthis oualaniensis) in the Waters of the Xisha Islands of the South China Sea

Abstract: In this study, we aimed to estimate the age, growth, and population structure to explore the life history of purpleback flying squid (Sthenoteuthis oualaniensis) by statolith microstructure in the waters of the Xisha Islands of the South China Sea. The purpleback squid, S. oualaniensis, has been the most important economic cephalopod resource of the South China Sea; however, little is known about its life history, especially its age and population structure. The age and growth pattern have been explored via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In this species, males reach maturity more quickly than females of the same age [58], a phenomenon also common in other Ommastrephidae species [59,60]. Previous studies have estimated the life span of S. oualaniensis in other areas of the South China Sea with statolith increments; these life spans have mostly been 1-4 months, except for squid collected in the western waters of the Philippines (life span: 95-275 days, 3-9 months) [23,24,26,27,61]. For example, the life span of squid in the Bashi Channel, the eastern tropical Pacific Ocean, the northern Pacific Ocean, and the Bay of Bengal is approximately 2-6 months (53-155 days, 84-168 days, 52-186 days, and 40-120 days, respectively) [22,25,62,63] (Table 2).…”
Section: Age Structure and Hatching Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…In this species, males reach maturity more quickly than females of the same age [58], a phenomenon also common in other Ommastrephidae species [59,60]. Previous studies have estimated the life span of S. oualaniensis in other areas of the South China Sea with statolith increments; these life spans have mostly been 1-4 months, except for squid collected in the western waters of the Philippines (life span: 95-275 days, 3-9 months) [23,24,26,27,61]. For example, the life span of squid in the Bashi Channel, the eastern tropical Pacific Ocean, the northern Pacific Ocean, and the Bay of Bengal is approximately 2-6 months (53-155 days, 84-168 days, 52-186 days, and 40-120 days, respectively) [22,25,62,63] (Table 2).…”
Section: Age Structure and Hatching Groupmentioning
confidence: 99%
“…Studies of the fishery biology and ecology of cephalopods found that the beak can help to determine taxonomy, age and growth patterns, and pigmentation, as well as to estimate biomass [18][19][20][21]. Previous growth studies have summarized the morphological characteristics and growth patterns of S. oualaniensis statoliths [22][23][24][25][26][27], but fewer studies have explored the growth pattern and pigmentation of S. oualaniensis beaks [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…2002), and their high economic development value in the Northwest Indian Ocean has been pointed out (Lu et al. 2022). India has launched an aspiring project to explore these resources from the southeastern Arabian Sea (Mohamed et al.…”
Section: Introductionmentioning
confidence: 99%
“…PBFS forms a target in commercial fishery in China (Lu et al. 2022) and is yet to be a part of the major cephalopod fishery in India. This may be attributed to the unconventional nature of this resource (Chembian 2013) and the oceanic lifestyle of oegopsid squids, which generally frustrates their sampling (Fernndez‐Alvarez et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of statoliths in the purpleback flying squid mainly focused on their microstructure [38][39][40], microchemistry [41], growth characteristics [18], morphological analysis [42][43][44], and the effects of life and growth patterns [24]. Studies regarding the discrimination of different geographical populations of purpleback flying squid based on statolith morphology mostly used traditional morphometry [42], whereas few employed Fourier transform and landmark methods [32].…”
Section: Introductionmentioning
confidence: 99%